Heidenzelte bei Aulaziwik, 80 km südlich von Killinek : [19--] - Lenz, Berthold, 1873-1960. (2001)
Black and white photograph of Inuit summer tents near Aulaziwik, 80 kilometres south of Killinek. Black and white photograph of Inuit summer tents near Aulaziwik, 80 kilometres south of Killinek.